MOTIVASI BELAJAR MAHASISWA POLITEKNIK NEGERI SRIWIJAYA PADA PROSES BELAJAR BAHASA INGGRIS SELAMA PEMBELAJARAN JARAK JAUH : SUATU STUDY NARATIF - MURWANI UJIHANTI; WELLY ARDIANSYAH; NURUL ARYANTI; AHMAD LEO FARAGUSTA; RISNAWATI RISNAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The energy that drives the spirit of learning is the motivation to learn. This motivation is fluctuating, sometimes strong and sometimes weak. Under normal circumstances, before the pandemic period, students came to class on time to take lessons. They can ask the teacher directly. Also, lecturers can see student responses directly, either implicitly or explicitly. Implicit responses can be seen from student gestures during the learning process in class. The problem that occurs is the arrival of a pandemic that causes all elements in the education system to suddenly have to adjust to new things. This change has an impact on changes in student learning motivation. The problem faced is the change in learning to the online system causes changes in students' learning motivation. These changes were studied using the descriptive inquiry method. The method of data collection was done by observing and describing